UPAYA PEMERINTAH DALAM MEMBERANTAS KORUPSI DI INDONESIA - Anandya, Shifra Sylvania; Indriani, Melisya; Efritadewi, Ayu; Widiyani, Heni (2024)
Efforts to eradicate corruption in Indonesia have been carried out in various ways, but until now there is still corruption in various ways carried out by various institutions. There are several dangers due to corruption, namely the danger to: society and individuals, the younger generation, politics, the nation's economy and bureaucracy. Corruption can harm society because it can damage justice, hinder development, and weaken trust in public institutions. Prevention and prosecution of corruption is an important focus in many countries to ensure good governance and social justice. In Undang-Undang Number 31 of 1999 concerning the Eradication of Corruption Crimes are classified into: harming state finances, bribery, embezzlement in office, extortion, fraudulent acts, conflicts in procurement, gratification. In order to eradicate corruption, it is necessary to carry out integrated enforcement, namely the existence of international cooperation and harmonious regulations.